Developing Swimmers - Brooks, Michael (Champaign, IL Human Kinetics, 2011)
This book will show you how to; evaluate and identify talent in even the youngest swimmers, establish realistic yet challenging short and long-term goals for your athletes, assess and refine strokes for greater power and efficiency, improve starts, turns, and finishes for faster times, structure positive and productive practices for swimmers and swim teams, and foster your swimmers' passion, bolster commitment, and instill winning attitudes.
Includes Illustration and Index
Keywords: Swimming -- Training